Trends in volume and risk profiles of patients undergoing isolated surgical and transcatheter aortic valve replacement. Issue 6 (30th September 2018) - Mori, Makoto; Bin Mahmood, Syed Usman; Geirsson, Arnar; Yun, James J.; Cleman, Michael W.; Forrest, John K.; Mangi, Abeel A.
Abstract : Background: Recent reports describe increases in the case volume of surgical aortic valve replacement (SAVR) after centers establish a transcatheter aortic valve replacement (TAVR) program. We investigate contemporary temporal trends in SAVR and TAVR case volumes and risk profiles at a high volume academic medical center. Methods: We conducted a retrospective, descriptive evaluation of consecutive patients who underwent TAVR ( n = 538) or SAVR ( n = 657) in 2011–2016. The STS predicted risk of mortality (PROM) for isolated SAVR was used to calculate PROM for both SAVR and TAVR patients. Patients were stratified based on STS PROM as follows: low risk (<4%), intermediate risk (4–8%), and high risk (≥8%). Temporal changes in patient risk‐profile were characterized descriptively. Results: Median STS PROM for the study period was 6.3% and 2.0% for TAVR and SAVR cohorts, respectively ( P < 0.001). Since 2011, TAVR volume consistently increased, while SAVR volume increased initially, peaking in 2013 and steadily declined. The STS PROM for SAVR remained stable during the entire study period, while that for TAVR showed a steady decline. The proportions of intermediate and low STS PROM patients undergoing TAVR increased. Proportions of each risk category in SAVR cohort remained stable over time. Conclusions: SAVR volume increased initially but declined eventually following the implementation of TAVR program. The distribution of the STS PROM in TAVR cohort changed dramatically with increasing proportion of patients in lower risk categories. These findings suggest the converging patient populations in TAVR and SAVR, which may be associated with the decline in the overall SAVR volume.